Synthesis of low-cost biomass charcoal-based Ni nanocatalyst and evaluation of their kinetic enhancement of MgH2. (22nd April 2022) - Hou, Quanhui; Zhang, Jiaqi; XinTao Guo,; Xu, Guanzhong; Yang, Xinglin
Abstract: In this study, a low-cost biomass charcoal (BC)-based nickel catalyst (Ni/BC) was introduced into the MgH2 system by ball-milling. The study demonstrated that the Ni/BC catalyst significantly improved the hydrogen desorption and absorption kinetics of MgH2 . The MgH2 + 10 wt% Ni/BC-3 composite starts to release hydrogen at 187.8 °C, which is 162.2 °C lower than the initial dehydrogenation temperature of pure MgH2 . Besides, 6.04 wt% dehydrogenation can be achieved within 3.5 min at 300 °C. After the dehydrogenation is completed, MgH2 + 10 wt% Ni/BC-3 can start to absorb hydrogen even at 30 °C, which achieved the absorption of 5 wt% H2 in 60 min under the condition of 3 MPa hydrogen pressure and 125 °C. The apparent activation energies of dehydrogenation and hydrogen absorption of MgH2 + 10 wt% Ni/BC-3 composites were 82.49 kJ/mol and 23.87 kJ/mol lower than those of pure MgH2, respectively, which indicated that the carbon layer wrapped around MgH2 effectively improved the cycle stability of hydrogen storage materials. Moreover, MgH2 + 10 wt% Ni/BC-3 can still maintain 99% hydrogen storage capacity after 20 cycles. XRD, EDS, SEM and TEM revealed that the Ni/BC catalyst evenly distributed around MgH2 formed Mg2 Ni/Mg2 NiH4 in situ, which act as a "hydrogen pump" to boost the diffusion of hydrogen along with the Mg/MgH2 interface. Meanwhile, the carbon layer with fantastic conductivity enormously accelerated the electron transfer. Consequently, there is no denying that the synergistic effect extremely facilitated the hydrogen absorption and desorption kinetic performance of MgH2 . Graphical abstract: The carbon layer is evenly wrapped around MgH2 /Mg, and Ni nano catalyst is evenly distributed on the surface. During dehydrogenation and reabsorption, Ni nanoparticles generate Mg2 Ni and Mg2 NiH4 in situ. The use of uniformly distributed Mg2 Ni/Mg2 NiH4 as a "hydrogen pump" promotes the diffusion of hydrogen along the Mg/MgH2 interface, and the carbon layer with good conductivity accelerates the electron transfer. It is believed that the synergistic effect of the two improves the hydrogen absorption and desorption rate of MgH2 . Image 1 Highlights: Biomass charcoal was introduced into the MgH2 system for the first time. Composites started to release H2 at 187.8 °C and could start to absorb H2 at 30 °C. The activation energy of de/hydrogenation was significantly reduced for composites. Biomass charcoal contributes to the cyclic stability of composites.